Collection Anthony Denney. - Desrois, Virginie; Mousseigne, Alain; Stadler, Rodolphe; Les Abattoirs, Toulouse (Genève - Milano : Skira editore, 2000)
Appel, Karel ; Assetto, Franco ; Brown, Jacques ; Burri, Alberto ; Coetzee, Christo ; Damian, Horia ; Dubuffet, Jean ; Falkenstein, Claire ; Fontana, Lucio ; Francis, Sam ; Francken, Ruth ; Imaï, Toshimitsu ; Jenkins, Paul ; Kalinowski, Horst Egon ; Kanayama, Akira ; Masanobu, Masatoshi ; Mathieu, Georges ; Nevelson, Louise ; Riopelle, Jean-Paul ; Saura, Antonio ; Serpan ; Shimamoto, Shozo ; Shiraga, Kazuo ; Sumi, Yasuo ; Tanaka, Atsuko ; Tàpies, Antoni ; Tchelitchew, Pavel ; Teshigahara, Sofu ; Uemae, Chiyu ; Vasarely, Victor ; Vedova, Emilio ; Yoshida, Toshi ; Yoshihara, Jiro
biog., tent., bibliog. per kunstenaar
Frans
boek